EXTENSION OF ELECTRIC LOCOMOTIVE OPERATION WITH USE OF NEW NEWEST MATERIALS IN CAPITAL REPAIR (Transport systems and technologies, 2018)
In the article, the analysis of the work of the traction engines and the reasons for their premature failure, which lead to unscheduled repair of electric locomotives and, accordingly, to spending money. Proposals for the complex modernization of traction electric cars, in particular the application of electrical insulation systems with the class of heat resistance H and C, as well as the replacement of the electrotechnical steel of the anchor core to the modern ones at 2212 and 1213, are offered. The propulsion engines operate practically continuously in the boundary conditions caused by voltage fluctuations in the contact network and the changes in the currents consumed, and the latter vary from 0, 25 / nm. to 2 / n. , which leads to even more power losses. The change in voltage in DC contact networks is respectively 2200 - 4000 V. All these facts create special requirements for the electric and mechanical strength of the traction motor units. The isolation of their windings in relation to the enclosure must withstand the test voltage U = (2.25U + 2000) B. For motors receiving power from a direct current contact network, U is equal to the idle speed at the engine's collector.
Keywords: traction motor, unscheduled repairs, traction electrical machines, electrical insulation system, class H and C heat resistance, electrical steel, armature core